Clinical Test of Pyrroles in Psychiatric Disorders: Association with Nutritional, Immunological and Metabolic Markers - Mikirova, Nina (Journal of Nutritional Therapeutics, 2015)
Background: Psychiatrists started using urine pyrroles (hydroxyhemopyrrolin-2-one, HPL) to diagnose psychiatric disorders many years ago. The biological origins of HPL are not known, nor are the causes of elevated urinary pyrrole excretion well understood. Methods: In the present study we analyzed the level of pyrroles in 148 patients with schizophrenia, 135 patients with bipolar disorder, 97 patients with depression, 119 patients with ADHD and compared these data with the results of pyrrole tests for patients with non-psychiatric conditions and healthy volunteers. Results: According to our data, urinary pyrrole concentrations tended to be high in patients with psychiatric disorders, but elevated level of pyrroles was not specific for only these patients. We found evidence of an allergy related component in the fact that elevated pyrrole levels were significantly more prevalent in subjects with elevated histamine values. A role of intestinal bacteria, or imbalances in intestinal bacterial metabolism, was also suggested based on the found relationship between elevated pyrrole levels and elevations in indicans and urobilinogens. In addition, our data demonstrated that subjects with severely elevated pyrrole levels were deficient in nutrients such as zinc, vitamin B3, and vitamin C. Conclusion: Thus, pyrrole excretion seems to be a component of illness in general and not strictly psychiatric disorders.